Characteristics of Fibrous Dysplasia at Oral and Maxillofacial Surgery Department RSUP Dr. Hasan Sadikin: A 6-year Retrospective Study - Prestya, Pebrian Diki; Hadikrishna, Indra; Sylvyana, Melita; Adiantoro, Seto; Rizki, Kiki Achmad (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Introduction: Oral and Maxillofacial surgeon encounter challenges diagnose fibrous dysplasia due to wide variety of investigations required, such as radiographic, histological, and clinical examinations. Fibrous dysplasia typically manifests at first or second decade of life; these lesions tend to form at young age and cease when somatic growth completed. Aim: The aim of this study understanding the characteristics of fibrous dysplasia in patients treated from 2017 to 2023 at Department of Oral and Maxillofacial Surgery Hasan Sadikin Hospital. Research Method: Design of this study is a qualitative descriptive study with retrospective using medical record data of patients diagnosed as fibrous dysplasia at Department of Oral and Maxillofacial Surgery of Hasan Sadikin General Hospital in January 2017 — March 2023. Variables in this study include age, gender, anatomical location at craniofacial area, histopathological diagnosis, and treatment provided. Results: This study showed Characteristics of fibrous dysplasia patients results by sex being highest in Women as many as 6 patients (54.54%), by age indicating the most age at 17-25 years old as 5 patients (45.45%). In addition, the highest prevalence based on histopathological diagnosis is monostotic type, which is 8 patients (72.72%) and three patients (27.27%) with polyostotic type. Based on the anatomical location the most at maxilla region, which is 7 patients, which is 5 (45,45%) patients at left maxilla region and 2 (18,18%) patients at right maxilla region. In addition, based on treatment the most was reshaping with 7 patients (63.63%).Conclusion: The most prevalent characteristic of patients with fibrous dysplasia is woman and by age indicating the most age at 17-25 years old. According to anatomical location the most is maxilla region. Monostotic fibrous dysplasia the most diagnose and the most prevalent treatmet is reshaping, which is the best therapy for of fibrous dysplasia.